2022
DOI: 10.3389/fimmu.2022.849468
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Protein Expression Is Associated With Good Clinical Outcomes and Nomogram for Prediction of Disease Free Survival and Overall Survival in Breast Cancer Patients Received Neoadjuvant Chemotherapy

Abstract: ObjectiveThis study aims to investigate the potential prognostic significance of programmed death ligand-1 (PD-L1) protein expression in tumor cells of breast cancer patients received neoadjuvant chemotherapy (NACT).MethodsUsing semiquantitative immunohistochemistry, the PD-L1 protein expression in breast cancer tissues was analyzed. The correlations between PD-L1 protein expression and clinicopathologic characteristics were analyzed using Chi-square test or Fisher’s exact test. The survival curve was stemmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…In Chen’s study, they performed that low PD-L1 protein expression was associated with significantly worse prognoses and shorter DFS and OS in breast cancer patients, and the protein expression of PDL1 was found to be a significant prognostic factor for patients who received neoadjuvant chemotherapy. 42 The results of this study were basically consistent with ours. Their enrolled patients were received neoadjuvant chemotherapy; however, our enrolled patients were stage III breast cancer without undergoing adjuvant therapy.…”
Section: Discussionsupporting
confidence: 92%
“…In Chen’s study, they performed that low PD-L1 protein expression was associated with significantly worse prognoses and shorter DFS and OS in breast cancer patients, and the protein expression of PDL1 was found to be a significant prognostic factor for patients who received neoadjuvant chemotherapy. 42 The results of this study were basically consistent with ours. Their enrolled patients were received neoadjuvant chemotherapy; however, our enrolled patients were stage III breast cancer without undergoing adjuvant therapy.…”
Section: Discussionsupporting
confidence: 92%
“…S2A–C ). Through immunohistochemical analysis and semiquantitative evaluation of VHL immunopositivity according to previous studies [ 25 , 26 ], we found that the expression of VHL was predominantly upregulated in renal epithelial cells (RECs) during CaOx nephrocalcinosis (Fig. S2D, E ).…”
Section: Resultsmentioning
confidence: 77%
“…The immunohistochemical score of VHL was performed using a semiquantitative system as demonstrated previously [ 25 , 26 ]. Briefly, histological analyses were performed by combining the density and intensity of positive staining cells.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that PD1, PD‐L1, TILs, and TMB may be potential biomarkers related to the efficacy of immunotherapy [ 19 , 20 , 21 , 22 ]. A French study retrospectively analyzed the correlation between TILs and clinical outcomes after immunotherapy and chemotherapy in patients with advanced nonsmall cell lung cancer (NSCLC), and the results showed that patients with high density of TILs had a lower risk of death and disease recurrence, and a higher ORR when treated with Nivolumab, while no similar phenomenon was observed in the chemotherapy group [ 23 ].…”
Section: Discussionmentioning
confidence: 99%